36 Feasibility of Resistance Exercise to Failure at Different Loads in Frail and Healthy Older Adults?. (16th March 2021) - Marshall-McKenna, R; Campbell, E; Ho, F; Banger, M; Rowe, P; McAlpine, C; McArthur, K; Quinn, T J; Gray, S R
Abstract: Introduction: Resistance training (RT) is the most effective way to increase muscle mass and function in older adults both with/without sarcopenia/frailty. In younger adults, when RT is performed to muscle failure the load lifted does not mediate the magnitude of response, but there are no studies in older adults. We aimed to determine the feasibility of recruitment to a RT intervention working to muscle failure at different loads in frail and healthy older adults. Methods: We performed an 8-week randomised feasibility trial of lower limb RT to volitional muscular failure, at high and low load. Participants were recruited via hospital outpatient clinics and newspaper advertisements. Outcomes included: frailty assessment (Fried criteria); muscle strength (maximum voluntary contraction/one-repetition maximum); functional abilities (Short Physical Performance Battery); safety/adverse events were recorded via a log, and patient experiences from focus groups. Results: 110 people were assessed for eligibility, and 58 randomised (frail n = 6, prefrail n = 20, robust n = 32) to either high (n = 30) or low load (n = 28) groups. Mean age of participants was 72 years (range 65–93), 36 were female, 22 male. Session attendance was 95% (high load) and 90.4% (low load). Most participants were recruited via advertisements. All participants reported feeling safe and reassured in the RT sessions. Two participants had a serious adverse event, one related to RT (hypotension) and several had adverse events (three intervention-related). Pain was reported at both loads (high n = 9, low n = 8) yet all completed. There were no differences (P > 0.05) in effects of RT outcome variables between low and high load groups. Conclusion: In this feasibility trial the recruitment of frail patients via clinics was limited. Performing supervised RT to muscle failure in older adults was safe/acceptable and the load at which RT was performed did not influence its efficacy. Future research into the effectiveness of such RT is warranted.